"Minor Setback, Major Comeback": A Multilevel Approach to the Development of Academic Resilience - Brandi N. Frisby (Central States Communication Association, 2021)
This study examined communicative processes at multiple levels that may influence students’ academic resilience through transitions. Participant interviews (N = 23) revealed that at the individual level, students develop a resilient mindset and effective academic strategies, engage in self-care, and compartmentalize. At the relational level, students rely on teachers to demonstrate positive teaching behaviors, receive academic and emotional support from a variety of sources, and find role models to inspire resilience. Finally, students reported that the campus community gave opportunities to build support networks and access campus resources, but identified threats to effective use of these resilience-building opportunities. Finally, all but one theme demonstrated that the development of academic resilience typically happens outside the traditional classroom yet affects student performance inside the classroom. These findings contribute to instructional communication research because of the application of an underutilized theory and method in instructional research, the multilevel focus on communication and resilience development processes, and by providing practical insight to create targeted approaches to improve student resilience and related outcomes.